REPRESENTASI NILAI MORAL PADA FILM BUDI PEKERTI KARYA WREGAS BHANUTEJA (KAJIAN SOSIOLOGI SASTRA) - Melysa, Melysa Putri Ayuningtyas; puspitasari, Indah (ASMARALOKA: Jurnal Bidang Pendidikan, Linguistik, dan Sastra Indonesia, 2024)
Movies not only entertain the audience, but also function as a means of conveying the messages they contain. Therefore, there are currently a lot of conversations about domestically and internationally produced films. The development of this movie has become a hot topic of conversation in the community. One of the movies that is currently hitting the audience is the movie 'Budi Pekerti' by Wregas Bhanuteja. The film tells the story of a guidance and counseling teacher who uses his unique technique to guide his students. Until one day, the teacher suddenly becomes a hot topic on social media. This affects his career and family. This drama genre movie presents realistic nuanced stories that are currently popular. The purpose of this research is to find out the moral values contained in the movie "Budi Pekerti". This research uses a qualitative descriptive method. The results of the research on the Budi Pekerti movie obtained by researchers are knowing the forms of cyberbullying and five moral values in the movie "Budi Pekerti". The five moral values are: honesty, hard work, creativity, critical thinking, and environmental care. Based on these five moral values, it can be concluded that the Budi Pekerti film is an educational spectacle and can instill good moral values for teenagers in the future.